Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Biologi Peserta Didik Kelas X MA Muhammadiyah Nangahure: Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Biologi Peserta Didik Kelas X MA Muhammadiyah Nangahure - Da Priska, Yuliana; Maria Ance Eting; Dian Ernangsih (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This study aim to determine the effect of inquiry learning model towards students learning outcomex of biology learning. This study was conducted in class X IPA of MA Muhammadiyah Nangahure. The method used was quasi experimental with one- group-pre test-post test design. The instrument used is test instrument inthe form of multiple choic questions as many as 10 item that used UN items. In this study the test data was obtained through pre test and post test to determine the achievement of students learning outcomes. The sample used was one class with a total of 21 students Before texting hypotheses using the t-test the test analysis pre requisites are first perfomed namely the normality test and homogenity test and the data are normally distributed and homogeneous Based on the hypotheses test perfomed obtained acount of 25,91 and t table of 1,72. Because t hitung > t tabel then HO is rejected and HI is accepted. Therefore the result of this study concluded that thereis an effect of inquiry learning model on students learning outcomes.